Remediating McLuhan - Cavell, Richard, 1949- (Book collections on Project MUSE., 2016)
"While current scholarly interest has assured McLuhan's foundational status as media theorist, it has by no means exhausted the import of his writings, which take on additional layers in the current digital moment. This collection of essays argues that it was McLuhan's confrontation of the bios that was the distinguishing feature of his media theory and the source of its most consistent problematic. Holding that media were extensions of the human, McLuhan also posited that the human was a product of technology. 'Remediating McLuhan' ranges over media theory, art history, bio-technology and deep history in addressing this problematic, and discusses McLuhan in the context of Flusser and Turing, Carl Woese and Daniel Lord Smail."--Back cover